(untitled) (Malaysian Journal of Civil Engineering, 2018)
Putrajaya river systems which consist of Sg. Chuau, Sg. Limau Manis and Sg. Bisa were ranked under multi criteria environment for future management. The rivers were ranked using multicriteria decision making approach, specifically applying Fuzzy Composite Programming (FCP). There are three main objectives of ranking; i) improving water quality, ii) enhancing water quantity and iii) minimising cost. The FCP structure contained 15 first-level indicators, six second level indicators, three third level indicators and one final indicator. Sensitivity analysis using four different set of weights were carried out to ensure the robustness of the options. Sungai Chuau was ranked the first with the highest ordered sequence value of 0.494. The highest ranking was determined based on the shortest distance between the fuzzy box and an ideal point. Sungai Chuau should be given the highest priority in the management and conservation of resources than the other river systems